(untitled) (Research, Society and Development, 2021)
In the laboratory research work, with drying taioba (Xanthosoma sagittifolium Schott) in different installations, in two drying systems, conventional dryer with resistive heating (50, 60, 70 and 80 ºC) and a prototype of a hygroscopic driver based on heat pump (25, 30, 35 and 40 ºC), the specific water removal rate (SMER) and the concentration of bioactive compounds: phenolic compounds, vitamin C and total chlorophyll were determined and determined. The heat pump dryer provided less degradation of the bioactive compounds, mainly vitamin C. In the conventional dryer, the lesser degradation of vitamin C was 80.6% at 60 ºC, while in the heat pump, the greater degradation was 70.3% at a temperature of 40 ºC. SMER increased with increasing drying temperature. SMER values vary between 3,465 and 8,551 kg of water/kWh for the heat pump and between 6,221 and 16,956 kg of water/kWh for the conventional dryer. The SMER of the heat pump at 40 ºC was higher than the SMER of the conventional dryer operating at 50 ºC.